ISOMORPHISM DALAM TRANSFORMASI DIGITAL INOVASI PELAYANAN PUBLIK - Nurmillah; Rusdin Nawi; Dahlan; Muhammad Nasir Mahmud (Journal Publicuho, 2024)
This research aims to investigate the patterns of isomorphism in the adoption of digital technologies in Indonesian government agencies, focusing on the variability of implementation and its impact on the harmonization of administrative practices and the efficiency of public services. The research method uses a qualitative approach with in-depth interviews and document analysis to collect data from various government agencies. The results of the analysis show that isomorphism facilitates inter-agency coordination but also presents challenges related to local innovation and adaptation. The implications of this research highlight the need for policies that support technology standardization while considering contextual variations to improve the responsiveness and quality of public services in Indonesia.